Legal Certainty Of Notary That Leave Because Inducted Into Legislature - Wella Tiara Aginta; Akhmad Khisni (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
The purpose of this study were 1) to analyze and explain the legal certainty of the notary who leave because inducted into the legislature. 2) To analyze and explain the barriers and solutions to the notary who leave because inducted into the legislature. The method used by researchers is normative legal approach and specification in this study were included descriptive analysis. The sources and types of data in this research is secondary data obtained from the study of literature. Based on the results of research that Legal certainty to the notary who leave because inducted into the legislature is always referred substitute notary replaced and the decree was not revoked. Normative, legal certainty it requires the availability of devices legislation which is operationally able to support its implementation. Empirically the existence of legislation that need to be consistent and inconsistent human resources and supporting Notary Supervisory Council. In the execution of a notary who leave because inducted into the legislative, which makes barriers in this issue, namely: a) Could not intensively guiding the deed made by the notary substitute; b) Can not make corrections formal and substantive evidence against the deeds were made but the name remained imprinted substitute notary; c) Can not guarantee against legal certainty to the deed made by the notary substitute; d) Can not / are not able to use the time off was good. Solutions to overcome barriers to notaries who leave because inducted into the legislature is to reinforce the requirement for nominating a member legislative, not just for not practicing (on leave) but with resignation as a notary or PPAT and release all the attributes (nameplate, office practices, and so on ).Keywords: Rule of Law; Notaries; Leave; Legislature.